Commuter lives: a review symposium on David Bissell's Transit Life. (28th November 2019) - Latham, Alan; Edensor, Tim; Hopkins, Debbie; Fitt, Helen; Lobo, Michele; Mansvelt, Juliana; McNeill, Donald; Bissell, David
Abstract: This article presents a series of commentaries on Transit Life: How Commuting is Transforming Our Cities, published by MIT Press in 2018. Centring on an in—depth case study of Sydney, the book argues the need to attend carefully to the fine—grained detail of the commuting experience. In all sorts of ways, Transit Life presents a way of thinking about urban transportation radically different from that used by mainstream transport planners and geographers. Geographical Research asked six researchers—Tim Edensor, Michele Lobo, Debbie Hopkins, Helen Fitt, Juliana Mansvelt, and Donald McNeill—to reflect on what kind of research vistas might be opened up bring the tools of cultural geography and mobility research to the world of commuting. Here are their responses, rounded out by a reply by David Bissell, Transit Life's author.